PSYCHOLOGICAL FOUNDATIONS FOR THE DEVELOPMENT OF TEACHERS’ PROFESSIONAL SELF-AWARENESS AND REFLECTIVE ACTIVITY IN THE DIGITAL PEDAGOGICAL ENVIRONMENT - Abdullaeva M. M. (Modern American Journals, 2025)
The study examines the psychological characteristics of youth as a dynamic social group undergoing continuous development in emotional, cognitive, and moral domains. In today’s rapidly changing world, young people face various challenges related to identity formation, value orientation, and social adaptation. Understanding these processes from a psychological perspective is essential for fostering resilience, creativity, and social responsibility among youth. The paper highlights the interplay between internal factors—such as motivation, emotional intelligence, and self-concept—and external influences, including family, education, digital media, and peer interaction. Emphasis is placed on the role of educational institutions in shaping positive self-identity and moral stability in young people through supportive psychological environments. The research also explores how globalization and digital transformation have redefined youth communication patterns, aspirations, and coping mechanisms. The findings contribute to the development of psychological-pedagogical strategies aimed at strengthening youth’s mental well-being, adaptive potential, and civic consciousness. By integrating theoretical perspectives and empirical insights, the study aims to guide educators and psychologists in creating conditions that promote holistic youth development and personal maturity.
Keywords: Youth, psychology, self-identity, emotional intelligence, motivation, social adaptation, digital environment, resilience, education, communication.